6‐year change in high sensitivity cardiac troponin T and the risk of atrial fibrillation in the Atherosclerosis Risk in Communities cohort. Issue 11 (21st September 2021) - Li, Linzi; Selvin, Elizabeth; Hoogeveen, Ron C.; Soliman, Elsayed Z.; Chen, Lin Y.; Norby, Faye L.; Alonso, Alvaro
Abstract: Background: Circulating high sensitivity cardiac troponin T (hs‐cTnT) is associated with incidence of atrial fibrillation (AF), but the association of changes in hs‐cTnT over time on incident AF has not been explored. Hypothesis: Six‐year increase in circulating hs‐cTnT will be associated with increased risk of AF and will contribute to improved prediction of incident AF. Methods: We conducted a prospective cohort analysis of 8431 participants from the Atherosclerosis Risk in Communities (ARIC) study. hs‐cTnT change was categorized at visit 2 and 4 as undetectable (<5 ng/L), detectable (≥5 ng/L, <14 ng/L), or elevated (≥14 ng/L). We used Cox regression to examine the association between the combination of hs‐cTnT categories at two visits and incident AF. We also assessed the impact of adding absolute hs‐cTnT change on risk discrimination for AF by C‐statistics and net reclassification improvement (NRI). Results: Over a mean follow‐up of 16.5 years, 1629 incident AF cases were diagnosed. Among participants with undetectable hs‐cTnT at visit 2, the multivariable HR of AF was 1.28 (95% CI 1.12–1.48) among those with detectable or elevated hs‐cTnT at visit 4 compared to those in which hs‐cTnT remained undetectable. Among those with detectable hs‐cTnT at visit 2, compared to those who remained in the detectable hs‐cTnT group, reduction to undetectable at visit 4 was associated with lower risk of AF (HR 0.74, 95% CI 0.59–0.94), while increment to elevated was associated with higher AF risk (HR 1.30, 95% CI 1.01–1.68). Adding hs‐cTnT change to our main model with baseline hs‐cTnT did not result in significant improvement in the C‐statistic or substantial NRI. Conclusion: Six‐year increase in circulating hs‐cTnT was associated with elevated risk of incident AF.